2016
DOI: 10.1111/jeb.12872
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational effects of nutrition are different for sons and daughters

Abstract: Food shortage is an important selective factor shaping animal life-history trajectories. Yet, despite its role, many aspects of the interaction between parental and offspring food environments remain unclear. In this study, we measured developmental plasticity in response to food availability over two generations and tested the relative contribution of paternal and maternal food availability to the performance of offspring reared under matched and mismatched food environments. We applied a cross-generational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 52 publications
(71 reference statements)
2
18
0
Order By: Relevance
“…Importantly, these effects were seen even with full outbreeding using unexposed C57BL/6J mice, compared with transgenerational studies where treated animals are bred to each other. Although differences by sex in F3 consequences are certainly recognized (Dew-Budd et al 2016;Zizzari et al 2016), the contribution of lineage transfer in relation to sex, and potential dynamic changes in response to ongoing environmental conditions, have received far less attention (Burggren 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these effects were seen even with full outbreeding using unexposed C57BL/6J mice, compared with transgenerational studies where treated animals are bred to each other. Although differences by sex in F3 consequences are certainly recognized (Dew-Budd et al 2016;Zizzari et al 2016), the contribution of lineage transfer in relation to sex, and potential dynamic changes in response to ongoing environmental conditions, have received far less attention (Burggren 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The lower nutrient requirements of the male mosquito probably allowed males to develop more quickly regardless of parental nutrition. A study conducted on the collembolan Orchesella cincta showed that parental nutrition did not influence male development time; however, it did influence male weight at maturity and the production of spermatophores [ 56 ]. When considering parental effects on Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Bonduriansky & Head, ; Mashoodh et al ., ; Crean & Bonduriansky, ; Zajitschek et al ., ; Fay et al ., ). For example, a father's diet influences offspring size and age at maturity in springtails (Zizzari et al ., ). This could be due to the presence of nongenetic factors in ejaculates, such as lipids and proteins that enter the zygote; or to epigenetic changes in paternal DNA that then affect gene expression in zygotes (Crean & Bonduriansky, ; Holman & Price, ).…”
Section: Introductionmentioning
confidence: 97%